Different Levels of Autophagy Activity in Mesenchymal Stem Cells Are Involved in the Progression of Idiopathic Pulmonary Fibrosis - Hongxia Tao; Qin Lv; Jing Zhang; Lijuan Chen; Yang Yang; Wei Sun (Hindawi Limited, 2024)
Idiopathic pulmonary fibrosis (IPF) is an age-related lung interstitial disease that occurs predominantly in people over 65 years of age and for which there is a lack of effective therapeutic agents. It has demonstrated that mesenchymal stem cells (MSCs) including alveolar epithelial cells (AECs) can perform repair functions. However, MSCs lose their repair functions due to their distinctive aging characteristics, eventually leading to the progression of IPF. Recent breakthroughs have revealed that the degree of autophagic activity influences the renewal and aging of MSCs and determines the prognosis of IPF. Autophagy is a lysosome-dependent pathway that mediates the degradation and recycling of intracellular material and is an efficient way to renew the nonnuclear (cytoplasmic) part of eukaryotic cells, which is essential for maintaining cellular homeostasis and is a potential target for regulating MSCs function. Therefore, this review focuses on the changes in autophagic activity of MSCs, clarifies the relationship between autophagy and health status of MSCs and the effect of autophagic activity on MSCs senescence and IPF, providing a theoretical basis for promoting the clinical application of MSCs.